2020
DOI: 10.1097/brs.0000000000003469
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perioperative Complications in Anterior Decompression With Fusion and Posterior Decompression With Fusion for Cervical Ossification of the Posterior Longitudinal Ligament

Abstract: Study Design. A retrospective comparative study. Objective. To compare the perioperative complications and costs of anterior decompression with fusion (ADF) and posterior decompression with fusion (PDF) for patients with cervical ossification of the posterior longitudinal ligament (OPLL). Summary of Background Data. Surgical treatment of cervical OPLL has a high risk of various complications. ADF and PDF are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Additionally, postoperative respiratory complications (PRC) can cause serious problems and major issues after ADF. Past reports indicate that postoperative adverse events of a respiratory nature, such as pneumonia and airway obstruction, occur in 0.6%-14% of patients after ADF [6][7][8]9) . Sometimes, accidental airway obstruction becomes a potentially life-threatening event that may require reintubation, for which one must be prepared with an effective management plan.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, postoperative respiratory complications (PRC) can cause serious problems and major issues after ADF. Past reports indicate that postoperative adverse events of a respiratory nature, such as pneumonia and airway obstruction, occur in 0.6%-14% of patients after ADF [6][7][8]9) . Sometimes, accidental airway obstruction becomes a potentially life-threatening event that may require reintubation, for which one must be prepared with an effective management plan.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Yoshii et al analyzed data from 2353 cases with cervical OPLL, of which 1333 cases underwent ADF and 1020 cases underwent PDF. Their report revealed that at least one local complication, such as cerebrospinal fluid leakage or surgical site infection, occurred in about 6.5% and 4.7% of anterior and posterior cases, respectively [24]. In cases with symptomatic cervical OPLL and/or DISH, including those with complications, the surgical outcomes were sometimes unsatisfactory; therefore, it is necessary to carefully monitor for neurological deterioration caused by the combination of multiple OSLs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is of great significance to develop individualized countermeasures by comparing the perioperative complications of CSWSCC patients with or without MRI T2WIHS. In order to effectively eliminate the error caused by selection deviation, we used the propensity matching score analysis method in this study [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%